Design and Development of a Fourwheeled Drive Multipurpose Prime Mover for Oil Palm Plantation Mechanization - El Pebrian, Darius (2009)
A new completely integrated machine system for mechanizing the field operations in the oil palm plantation in Malaysia has been successfully designed, developed and evaluated. The machine system consists of a 4WD multi purpose prime mover associated with its machine attachments for circle spraying, blanket spraying and infield FFB collection-transportation operation and provisions for the other future machine attachments. Computations were made to predict the overall performances of the proposed 4WD multi purpose prime mover based on the terrain parameters obtained from the study on the mechanical terrain properties. Computations also were made to estimate on the overall hydrostatics efficiency of the prime mover, and the required hydraulic pressure for operating all actuators within the respective machine attachments. Besides, a study on machine and human performances in oil palm cultivations in Malaysia has been sucessfully conducted to identify the critical field operations or tasks within the nursery and field stage operations prior to establishing the design concept of the 4WD multipurpose prime mover with its respective machine attachments. The greater priority was given to the identified critical field operations and the identified tasks within the operation in designing and developing the types of machine attachments for the 4WD multi purpose prime mover. The attachments for spraying operations and in-field FFB collection-transportation operation were given a greater priority to be designed and developed to complete the functionality of the prime mover in order to be a universal prime mover. Results from field evaluations had showed that the average effective field capacity for the circle spraying operation with the machine system was found to be 0.98 ha/hr or equal to 7.89 ha/man-day with 8 committed working hours per day or increments of average effective machine field capacity of 1.97 over the Serena LT16 knapsack sprayer. The average effective field capacity for the blanket spraying operation with the machine system was found to be 3.82 ha/hr or equal to 30.61 ha/man-day with 8 committed working hours per day or increments of average effective machine field capacity of 1.53 times over the mini-tractor with fully mounted 10 m boom sprayer. The average machine output of in-field FFB collection-transportation operation with the machine system operating on gently undulating terrain was 2.620 ton/hr or equal to 20.965 ton/day with 8 committed working hours per day. An average machine output increment of 3.58% higher than average machine output of 2.526 ton/hr or equal to 20.213 ton/day was obtained when the machine system operating on sloping terrain.A spraying cost increment per hectare of 24.90% or an additional cost of RM5.36/ha (1.53 USD/ha) was obtained in circle spraying operation with the prime mover over the Serena LT16 knapsack sprayer. Increasing the effective field capacity of the machine system to a value equal or greater than 1.33 ha/hr (i.e. 26.3% increased) or reducing the initial cost of the machine system to RM27,500 (USD 7714.28) or 0.41 times reduction would qualify the machine system to be cost effective over the Serena LT16 knapsack sprayer for circle spraying operation. A spraying cost reduction per hectare of 19.54% or a cost saving of RM1.54/ha (0.44 USD/ha) was obtained in blanket spraying operation with the prime mover over the mini tractor with fully mounted 10 m width boom sprayer. An operating cost reduction in the range of 6.74% to 14.25% per ton or cost savings in the range of RM0.62/ton (0.18 USD/ton) to RM1.31/ton (0.37 USD/ton) were obtained in in-field FFB collection-transportation operation with the prime mover over the mini tractor-trailer with grabber. In-field FFB collection-transportation operation by the prime mover with in-field FFB collection-transportation attachment was 63.35 times more exhausting on basis of the measured human energy expenditure, 1.59 times more demanding on basis of the measured mean increase in heart rate, and 1.16 times less dawdling on basis of the measured average field capacity than the operation by the mini tractor-trailer with grabber.Circle spraying operation by the prime mover with circle spraying attachment was 0.89 times less exhausting on basis of the measured of the human energy expenditure, 0.32 times less demanding on the basis of the measured mean increase in heart rate and 1.78 times less dawdling on the basis of the measured average field capacity than the operation by the Serena LT16 knapsack sprayer.